CYSTIC FIBROSIS AND PSYCHOLOGICAL ASPECTS: CASE REPORT. (Fiep Bulletin - online, 2014)
The cystic fibrosis is a hereditary chronic illness, that can compromise, in the patient, its gastric intestinal, respiratory, nutritional, psychological and pertaining to school functioning, beyond having reserved prognostic, having emotional repercussions in such a way in the patient as in its family, that can in accordance with aggravate the level of the illness, with the necessity of hospital intervention and the proper psychological balance of the patient and of its family. In such a way, the present work approaches involved psychological aspects in cystic fibrosis (FC), describes the main factors of the psychological attendance carried through to the fibrosis patient and its familiar ones in hospital environment, with the general objective of assisting the diagnosis and the therapeutically one of these patients in the scope of Psychology. Concluded that it has important benefits of the psychological intervention for the patient and its family.
Keywords: cystic fibrosis; child; psychological aspects